A digital seismogram archive of nuclear explosion signals, recorded at the Borovoye Geophysical Observatory, Kazakhstan, from 1966 to 1996. (June 2015) - An, Vadim A.; Ovtchinnikov, Vladimir M.; Kaazik, Pyotr B.; Adushkin, Vitaly V.; Sokolova, Inna N.; Aleschenko, Iraida B.; Mikhailova, Natalya N.; Kim, Won-Young; Richards, Paul G.; Patton, Howard J.; Scott Phillips, W.; Randall, George; et al.
Abstract: Seismologists from Kazakhstan, Russia, and the United States have rescued the Soviet-era archive of nuclear explosion seismograms recorded at Borovoye in northern Kazakhstan during the period 1966–1996. The signals had been stored on about 8000 magnetic tapes, which were held at the recording observatory. After hundreds of man-years of work, these digital waveforms together with significant metadata are now available via the project URL, namelyhttp://www.ldeo.columbia.edu/res/pi/Monitoring/Data/ as a modern open database, of use to diverse communities. Three different sets of recording systems were operated at Borovoye, each using several different seismometers and different gain levels. For some explosions, more than twenty different channels of data are available. A first data release, in 2001, contained numerous glitches and lacked many instrument responses, but could still be used for measuring accurate arrival times and for comparison of the strengths of different types of seismic waves. The project URL also links to our second major data release, for nuclear explosions in Eurasia recorded in Borovoye, in which the data have been deglitched, all instrument responses have been included, and recording systems are described in detail. This second dataset consists of more than 3700 waveforms (digital seismograms) from almost 500 nuclear explosions in Eurasia, many of them recorded at regional distances. It is important as a training set for the development and evaluation of seismological methods of discriminating between earthquakes and underground explosions, and can be used for assessment of three-dimensional models of the Earth's interior structure.